Dasheen to market - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Guide to producing and handling export quality dasheen in the OECS. G C Robin, CARDI/CTA. 2000. 12 pp. ISBN 976 617 005 3 CTA number 989. 5 Credit points